PUBLIC COUNCILS AS AN INSTITUTION FOR ENHANCING PUBLIC TRUST IN THE JUDICIAL SYSTEM OF UKRAINE - KOVBAS, IGOR (Ehrlich's Journal, 2025)
The article is devoted to the study of the functioning of public councils and their role in the process of reforming Ukraine’s judicial system. The interaction between the judiciary and civil society institutions through public councils is analyzed. The research examines the relationships between civil society institutions and the judicial system in the context of the modernization of Ukrainian society and the state. The purpose of this study is to identify opportunities for implementing civilized aspects of interactions between public authorities and civil society. The article highlights the dynamics of the development of public councils and the current state of the legal and regulatory framework in this field. It demonstrates that public councils serve as a powerful tool for engaging citizens in public administration and can become an effective communication mechanism between public authorities and society, provided there is an active civic position and a responsible approach to fulfilling the obligations and powers undertaken by all participants in the communication process. Theoretical and legal foundations of the interaction between government bodies and the public are summarized. The main forms, methods, and tools of such interaction are identified. Recommendations are formulated for improving the organization and conduct of public consultations on the development and implementation of state policy. The article emphasizes the importance of public oversight for the establishment of a democratic society and reveals the mechanisms through which it can be implemented. The author concludes that public councils, as temporary consultative and advisory bodies, contribute to public participation in judicial reform and constitute an integral part of a democratic society. A conceptual understanding of the legal foundations and operational mechanisms of public councils in the context of judicial reform is proposed to ensure the effective administration of justice.